Combining gold nanoparticle antennas with single-molecule fluorescence resonance energy transfer (smFRET) to study DNA hairpin dynamics. Issue 14 (26th March 2018) - Hu, Jinyong; Wu, Meiyan; Jiang, Li; Zhong, Zhensheng; Zhou, Zhangkai; Rujiralai, Thitima; Ma, Jie
Abstract : Gold nanoparticle antennas as a promising platform not only for fluorescence enhancement but also for the studies of single-molecule kinetics. Abstract : The association of a plasmonic nano-antenna with single-molecule FRET technique presents new prospects to investigate the dynamics of biological molecules. However, the presence of a plasmonic nano-antenna significantly modifies the FRET rate and efficiency; this makes its applicability to the prevalent single-molecule FRET experiments unclear. Herein, using gold nanoparticle antennas of different sizes and DNA hairpins labelled with FRET pairs (Cy3 and Cy5) as the model system, we performed experiments to study the folding dynamics of single DNA hairpins at various salt concentrations. Our results indicate that gold nanoparticle antennas can enhance single-molecule fluorescence of Cy3 and Cy5 up to 3–5 folds, substantially reduce the FRET efficiency, and alter the obtained FRET efficiency histograms. However, the folding dynamics of DNA hairpins remains unaffected, and the correct kinetic and dynamic information can still be extracted from the seriously modified FRET efficiencies. Therefore, our experiments demonstrate the feasibility and compatibility for applying plasmonic nano-antennas to the mostly used single-molecule FRET assays, which provide a broad range of possibilities for the future applications of these nano-antennas in studying various essential biological processes.